Penatalaksanaan Okupasi Terapi Menggunakan Behavior ModificationDalam Aktivitas Menyikat Gigi Pada Kasus Keterbatasan IntelektualTaraf Sedang Di Panti Sosial Bina Grahita Ciungwanara Bogor - Wicaksono, Gunawan; Ulkhusna, Fatwa Sari; Betty, Purnama (Jurnal Vokasi Indonesia, 2018)
Intellectual disability is a disabilities with limitaton in intellectual function, adaptive function, and the onset must occur before the age of 18 years. This study focus on Ja 19 years old with moderate intellectual disability that have difficulty in ability of oral hygiene is toothbrushing. The aim of the process of writing is to find out how occupational therapy intervention in increase of patient skill to maintenance his oral hygiene with toothbrushing using behavior modification. Data obtained from interviews, observation, assessment, and occupational therapy intervention. The result show that the effectiveness of behavior modification will be find out if the programs will be doing consistently.